KARAKTERISTIK PETANI PADI PESERTA PROGRAM UPAYA KHUSUSPADI JAGUNG KEDELAI UPSUS PAJALE DI DESA RANAH BARU KECAMATAN KAMPAR KABUPATEN KAMPAR - Hidayat, Tommi; Yulida, Roza; Rosnita, Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research is intended to understand the characteristic of the farmers, stage on the Specially Efforts Corn, Soybean, Paddy (UPSUS PAJALE) at RanahBaru village. This research was conducted at RanahBaru village that is located in the Kampar Regency. Multi stage sampling was used as the method to choose locations. The samples were gathered using Purposive Sampling method. This research uses 82 farmers data as samples. Data analysis which is used for this research is the descriptive method. The goals were analyzed using Likert Scale. The results of this research shows us the paddy farmers’ internal characteristics at RanahBaru village such as: the farmers’ productive ages are within the range of 43-49 years, most of the farmers’ are High School graduates, each farmers’ family consists of 4-5 persons, farmers’ experiences are between 13-17 years, the land area that the farmers manage is between 0,5-0,75 ha and the farmers are highly cosmopolitans. The external characteristics of farmers are highly when are evaluated according to the instructors’ intensity, the accuracy of instructors channel, the amount of information sources, the affordability of production facilitiesprice and the availability of production facilities. Keywords:Internal characteristics, External characteristics,Specially Efforts Paddy, Corn, Soybean, (UPSUS PAJALE)